The Influence of Fashion Lifestyle, Promotion, and Service Quality on Purchase Intention Among Consumers of the Giyomi Fashion Brand in Surabaya - Savira Az Zahro; Indah Respati Kusumasari (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to analyze the influence of fashion lifestyle, promotion, and service quality on purchase intention among consumers of Giyomi Fashion Brand Surabaya. This research employed a quantitative approach with an associative research design. The sampling technique used purposive sampling with a total of 112 respondents who were consumers of Giyomi Surabaya. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with SPSS. The results revealed that fashion lifestyle, promotion, and service quality simultaneously had a significant effect on purchase intention. Partially, fashion lifestyle had a positive and significant effect on purchase intention with a significance value of 0.005, promotion had a positive and significant effect with a significance value of 0.000, and service quality had a positive and significant effect with a significance value of 0.002. Among the independent variables, promotion was identified as the most dominant factor influencing consumers’ purchase intention. This study contributes to the development of consumer behavior studies in the local fashion industry, particularly regarding the role of fashion lifestyle, promotion, and service quality in influencing consumers’ purchase intention.